Meningkatkan Pemahaman Siswa dalam Menyelesaikan Soal Cerita tentang Denah Berskala dengan Metode Tutor Sebaya di Kelas V SDN 34/I Teratai - Destrinelli, Destrinelli; Susanto, Agustian; Nofriani, Endang; Nabila, Nabila; Pratiwi, Novia Anggun (Lembaga Yasin AlSys, 2023)
Education is an important factor in the development of a country. One of the goals of education is to develop students' intellectual abilities and understanding in various fields. In the process of learning mathematics, students' understanding of solving word problems is very important. Word problems provide a real context for students in applying mathematical concepts to everyday life. The purpose of this study was to measure the level of students' understanding in solving word problems about scale plans in Grade V SD. The research was conducted at SDN 34/I Teratai, Muara Bulian District, Batang Hari District. When the research was carried out in the odd semester of the 2022/2023 school year. This research was used in Mathematics Class V semester 1 with the material for solving story problems about Scaled Plans. This research cycle consists of planning, action, observation, and reflection which is done repeatedly until the achievement indicators for this CAR can be achieved. As subjects in this classroom action research were students of Class V SD 34/I Teratai. The number of students who were used as research subjects was 23 people, consisting of 10 men and 13 women. The object of this study was the application of the Peer Tutor Method. Data collection techniques are observation, tests, interviews and documentation. This research was carried out in cycles with each cycle consisting of four components, namely: planning, action and observation, and reflection. After the cycle has been implemented, especially after reflection, it is then followed by re-planning which is carried out in the form of a separate cycle.